2020
DOI: 10.1002/ajcp.12470
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Providers’ Work Engagement and Burnout in Homeless Services: A Cross‐national Study

Abstract: • The complexity of users' characteristics can make working with homeless people very stressful. • Some features of homeless services are likely to be associated with providers' well-being. • Useful training was associated with higher levels of work engagement and lower levels of burnout. • Non useful supervision was positively associated with providers' burnout. • Capability-fostering approach was positively associated with providers' well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…While burnout is significant in the homelessness sector, there is evidence to suggest that organizations can play a role in protecting workers against burnout. One study found that availability of perceived relevant training was positively associated with service provider work engagement and negatively associated with burnout [ 31 ]. Another study introduced the “Florence Nightingale effect” that higher perceived client suffering was correlated with higher job satisfaction and lower burnout among staff, and this relationship was mediated by greater identification with the organization [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While burnout is significant in the homelessness sector, there is evidence to suggest that organizations can play a role in protecting workers against burnout. One study found that availability of perceived relevant training was positively associated with service provider work engagement and negatively associated with burnout [ 31 ]. Another study introduced the “Florence Nightingale effect” that higher perceived client suffering was correlated with higher job satisfaction and lower burnout among staff, and this relationship was mediated by greater identification with the organization [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an organisational ethos which encourage feelings of efficacy and control, as well as good supervision and managerial support (Adams et al., 2006; Lloyd et al., 2002), are likely to lead to higher levels of job satisfaction and provide a protective buffer against STS (Berger et al., 2015; Hinderer et al., 2014; Makic, 2015). Similarly, provision that instils or facilitates appreciated collegial and supervision support is equally beneficial (Drüge & Schleider, 2016; Kidd et al., 2007; Lenzi et al., 2020; Stalker et al., 2007; Wirth et al., 2019). In addition, commitment to an organisational ‘identity’ can play a significant supporting role.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kosny and Eakin (2008) (Schön, 1983) and TIC values being central to PIE approaches (Cockersell, 2011;Johnson & Haigh, 2010;Phipps et al, 2017), this finding highlights the need for the host organisation to proactively address these engagement challenges. Additional initiatives are needed to highlight and share identified support needs with staff and to promote their relevance for personal well-being and practice (Lenzi et al, 2020).…”
Section: Perceptions Of the Quality Of Support Of Client Needs Experi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Organisational and individual personal factors can contribute to staff wellbeing. Organisational factors include management support, positive team dynamics and reflective practices [ 20 , 21 ]. Reflective practice refers to formal or informal arrangements that support staff to reflect honestly and openly on the emotional components of their work [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%